HUBUNGAN KONDISI LINGKUNGAN PERUMAHAN DENGAN KEJADIAN DIARE DI DESA SIALANG BUAH KECAMATAN TELUK MENGKUDU KABUPATEN SERDANG BEDAGAI TAHUN 2012 - Fiesta Oktorina Sinaga; Surya Dharma; Irnawati Marsaulina (Lingkungan dan Kesehatan Kerja, 2013)
The relationship condition of housing’s environment with the incidence of diarrhea in the Sialang Buah Village Teluk Mengkudu Sub District Serdang Bedagai District  2012. Diarrhea is a public health problem in developing countries such as Indonesia. Based on data from Department of Health Serdang Bedagai District, in 2011, diarrhea was ranked second after ISPA. In Sialang Buah Public Health Center recorded  the highest  incidence of diarrhea was occured range of age 1 month-1 year around 154 cases and 1 year-4 year around 140 cases. This study aims to determine the relationship condition of housing’s environment with the incidence of diarrhea in the Sialang Buah Village Teluk Mengkudu Sub District Serdang Bedagai District  2012. This method of research was an analytic survey with a  cross sectional study design. The sample of this research were 88 housewives  who have children 0-5 years old with proportional random sampling technique. Data were analyzed with chi square test. The value of statistical confidence is 95% and the value of significance (α) 0,05. The results showed that the variables related to the incident of diarrhea under 5 years old in Sialang Buah Village are availability of latrine (p = 0,005), exclusive breastfeeding (p = 0,009), Using health latrine (p = 0,003), and handwashing with soap (p = 0,006). Variables that are not associated with the incident of diarrhea are availability of clean water, wastewater disposal facilities, waste disposal facilities, house floor, density of flies, food storage facilities, corral, and using clean water (p>0,05). Recommendation for the health center and Department of Health to better socialize more about diarrhea diseases by improving health promotion about diarrhea, basic sanitation, clean of residential environment so the society will keep clean the environment, also clean and healthy behavior to the villagers. For housewives who have children under 5 years old to better maintain and improve clean and healthy behavior in the household. Key words: Condition of housing’s environment, incidence of diarrhea